2010
DOI: 10.1177/0733464810387578
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Older Person in the Context of Delivery and Receipt of Home Support

Abstract: Client perspectives of home support (i.e., assistance with daily activities that help to maintain a safe and supportive home) have not been considered in relation to personhood: "a standing or status that is bestowed upon one human being, by others, in the context of relationship and social being." Personhood and positive person work interactions conceptually guided our secondary analysis of data from a generic qualitative study including 82 semi-structured interviews with older adult home support clients in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…Twelve articles (Ek et al, 2011;Liveng, 2011;Breitholtz et al, 2012Breitholtz et al, , 2013aByrne et al, 2012;Doyle, 2012;Holmberg et al, 2012;Swedberg et al, 2012;Witsø et al, 2012;Glasdam et al, 2013;Moe et al, 2013;Hillcoat-Nall etamby, 2014) are included and distributed across the following nationalities: Sweden (5) Norway (2) Denmark (2) Canada (1) Wales (UK) (1) Australia (1). All countries have home care and legislation which respects people 0 s right to self-determination.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles (Ek et al, 2011;Liveng, 2011;Breitholtz et al, 2012Breitholtz et al, , 2013aByrne et al, 2012;Doyle, 2012;Holmberg et al, 2012;Swedberg et al, 2012;Witsø et al, 2012;Glasdam et al, 2013;Moe et al, 2013;Hillcoat-Nall etamby, 2014) are included and distributed across the following nationalities: Sweden (5) Norway (2) Denmark (2) Canada (1) Wales (UK) (1) Australia (1). All countries have home care and legislation which respects people 0 s right to self-determination.…”
Section: Resultsmentioning
confidence: 99%
“…Perceptions of home support were contingent upon the personalities, attitudes, and training of the worker(s) who delivered care. Clients want to know their workers and want their workers to know them (Aronson, 2004;Byrne et al, 2010). Agencies can support this through providing basic training in care that promotes personhood and by establishing clear guidelines around strategies for respectful communication and positive interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…This article is based on a larger study aimed at understanding the key issues in the delivery and receipt of home support services from the perspective of HSWs, elderly clients, and family members (Byrne, Frazee, Sims-Gould, & Martin-Matthews, 2010;Sims-Gould, Byrne, Craven, Martin-Matthews, & Keefe, 2010;Martin-Matthews & Sims-Gould, 2008;Sims-Gould & MartinMatthews, 2010a, 2010b. The qualitative portion of the study consisted of interview data from clients and families who responded to open-ended questions about their home care services.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, complaints are legion that mental health provision is poorly integrated with wider physical health and social care services, despite the frailty and multimorbidity common amongst this patient group . At an interpersonal level, it is known that communication with care workers has the potential to either reinforce or compromise an older person's identity and selfhood, especially in the context of cognitive decline, depending on how it is delivered . Indeed, for patients with dementia and their carers, preference studies have indicated that continuity of care is prioritised above other features, supporting the argument that relational aspects of care are crucial to wellbeing in this population.…”
Section: Introductionmentioning
confidence: 99%